Design, construction, and analysis of pavements using accelerated loading facility - Roberts, Freddy L. 1941-2007 (Transportation Research Board of the National Academies, 2007)
Resumen: Presenta la construcción de una instalación de pavimento de ensayos a escala natural con la instalación de carga acelerada (ALF) de la máquina por el Louisiana Transportation Research Center